Environmental Communication Media Exposure and Behavioral Change: - Wenas, Jayanti; Stefany, Stella (UPT Publikasi Ilmiah UNISBA, 2023)
A high amount of plastic waste and its threats to the environment and living things have become a major concern for many countries. One of the causes is the widespread use of single-use plastic bags in our everyday lives. Various studies have examined the negative impacts of plastic waste, and many environmental activists have responded to this global concern. Seasoldier is a community that has been conducting a digital campaign by utilizing the hashtag #Seasoldier to encourage followers to reduce their use of plastic bags. This study aims to determine the correlation between media exposure of #SeaSoldier on Instagram and behavioral change in their followers, and to examine the Media Ecology theory in an environmental communication context. A purposive sampling technique was applied to obtain respondents who met the following criteria: having an Instagram account and being an active follower of Seasoldier. The result of this study indicates a positive and strong correlation between the use of the hashtag feature and behavioral change, with a correlation coefficient value of r=.776 and a coefficient determination value of r2=.598, which defines 59.8% of the hashtag campaign exposure as leading to changes in followers’ behavior. Future research can develop broader research on the factors influencing follower behavior using qualitative methods.